Factors Associated with Non-Use of Contraceptives among Married Women in Nepal - Adhikari, Ramesh; Acharya, Devaraj; Ranabhat, Chhabi Lal; KC, Ranju (Journal of Health Promotion, 2019)
Most of the family planning services are being provided free of cost in Nepal however threat of service utilization appears unsatisfactory. This paper aims to assess the factors that are associated with non-use of family planning services among currently married women of reproductive age. The data for this paper are extracted from the Nepal Demographic and Health Survey (NDHS), 2016. Altogether 9875 currently married women of reproductive age were included in this analysis. Bivariate and multivariate analysis were performed to explore the association of socio-demographic characteristics with non-use of contraceptives. Almost a half of the sampled currently married women (47%) were non-users of contraception. Married women aged below 25 years (aOR=2.07, 95% CI 1.75-2.44) and aged 25 to 34 year (aOR=1.15, 95% CI 1.02-1.29)were more likely to not to use contraceptives compared to women aged 35 or above years. Janajati were less likely to be non-user of contraception compared to Brahmin/Chhetri (aOR=0.73, 95% CI 0.64-0.83). Muslim women were less likely to use contraception (aOR= 2.45, 95% CI 1.9-3.2) compared to Hindu women. Likewise, women who did not work currently were more likely to not use contraceptives compared to currently working women (aOR=1.47, 95% CI 1.32-1.63).Similarly, poor women were less likely to not use contraception compared to rich women (aOR=1.15, 95% CI 1.01-1.32).Similarly, women who had no autonomy were more likely to be non-user of contraceptive (aOR=1.16, 95%CI 1.01-1.32) than those how had high autonomy. Women who had not heard family planning message from TV in last few months were more likely to not use contraceptives (aOR=1.16, 95%CI 1.02-1.31) than those who had heard after controlling other socio-economic variables. Women aged less than 25 years, Muslim women, currently not working and having poor wealth status, having no autonomy in household decision making, who did not watch FP message in TV were more likely to not use contraceptive methods compared to their counter parts. Thus, family-planning-related interventions need to be more focused among younger aged women, women having no or less autonomy in decision making, poor and jobless women and Muslim women. Furthermore, women empowerment initiatives (employment opportunities) tied up with family planning programs would be beneficial to increase contraceptive uptake among married women of reproductive age.